Radium-223 for the treatment of castration-resistant prostate cancer - El-Amm, Joelle (2015)
The vast majority of patients with metastatic castration-resistant prostate cancer (mCRPC) develop bone metastases. Bone metastases are a source of significant morbidity and affect quality of life in these patients. Several bone-targeting agents are approved for the treatment of bone metastases in prostate cancer, including bisphosphonates, denosumab, and radiopharmaceuticals. Radium-223 is a novel first-in-class alpha-emitting radiopharmaceutical that has been approved for treatment of patients with mCRPC with bone metastases. Radium-223 delivers cytotoxic radiation to the sites of bone metastases and offers the advantage of minimal myelosuppression. The landmark Phase III ALSYMPCA trial demonstrated that, in addition to providing bone-related palliation, radium-223 can also prolong overall survival in patients with mCRPC with bone metastases in the absence of visceral metastases and in the absence of lymphadenopathy greater than 3 cm. Ongoing trials will further elucidate its use in sequence or combination with other available therapies for mCRPC.